Improvement of nitrogen fertilizer efficiency using enhanced efficiency fertilizer urea on maize production - Noor Affendi, Nur Mahfuzah (2017)
The application of urea fertilizer has always been an issue due to the loss of N of up to 50% and insufficient uptake by plants. Urea when applied to soils hydrolyzes rapidly into ammonium and the subsequent accumulation of ammonium in soil results in high pH at the urea microsites which favor ammonia (NH3) volatilization. Meanwhile, the remaining ammonium undergoes nitrification and subsequently contributes to nitrous oxide (N2O) emissions through denitrification. Improving N fertilizer efficiency is therefore extremely crucial to minimize environmental and economic losses. Among the possible approaches is to amend urea to enhance its efficiency or by producing Efficiency Enhanced Fertilizers (EEF) by coating urea with urease and nitrification inhibitors. In this study Cu and Zn were used as urease inhibitors while 3,4-dimetylphosphate (DMPP) was used as the nitrification inhibitor. The objectives of this study were to determine the timing of N uptake by maize at different growth stages and to determine the effects of the newly developed Enhanced Efficiency Fertilizer (EEF) on N transformation, NH3 volatilization and N2O emission when applied to selected soil series and to determine the effects of these fertilizers on crop production and N uptake by maize in the glass house and under field conditions. Laboratory, glass house and field studies were conducted to evaluate the EEF treatments. The 15N isotope was used to measure the nutrient use efficiency (NUE), nitrogen derived from fertilizer (NDFF) and nitrogen derived from soil (NDFS) using the Munchong soil series and maize as the test crop. This technique was used to determine the timing for N uptake in maize at different growth stages. The enrichment of 15N in the plants was determined using emission spectrometry. The results of this study revealed that the N fertilizer uptake by the maize peaked in the 8th week after planting after which N fertilizer uptake gradually decreased. The maize was more dependent on soil N at the early stages of its growth. However, more N fertilizer was used during the active vegetative growth stage until maturity. The Nitrogen use efficiency of the maize was low, at 37% of the applied urea, and the NDFF and NDFS were 60% and 40%, respectively. In the laboratory and glasshouse studies, ten treatments of EEF were included and labeled as: urea (control); UCu (Cu coated urea); UZn (Zn coated urea); UCuZn (Cu and Zn coated urea); UDMPP (3,4-dimetylphosphate (DMPP) coated urea); UCuDMPP (Cu and DMPP coated urea); UZnDMPP (Zn and DMPP coated urea); UCuZnDMPP (Cu, Zn and DMPP coated urea); Ubio (biochar impregnated with urea); and Ug2 (geopolymer coated urea). Urea was coated with Cu, Zn and DMPP using palm stearin. Laboratory evaluation was carried out to study the N transformation, NH3 loss and N2O emission on the selected soil series, the Munchong and Serdang soil series. The applications of EEF treatments with micronutrients (Cu and Zn) and DMPP were effective in reducing urea hydrolysis and the nitrification process. The UCuZn resulted in 157.49 μg g-1 NH4 content and 9.07% of NH3 loss which were significantly lower than that for the control, by 54.24% and 57.76%, respectively. On the other hand, the UCuZnDMPP treatment emitted the lowest N2O among all the treatments with the value 27.44 μg g-1, 60.62% lower in comparison to the control treatment. The Serdang and Munchong soil series were used to grow the Mas Madu maize variety under glasshouse conditions. The plants were harvested after 9 weeks. The Urea (control) and EEF treatments, triple super phosphate and potassium chloride were applied as N, P and K sources at the rate of 120, 50 and 100 kg ha-1, respectively, one week after direct sowing, with two applications of the EEF treatments throughout the growing period. The NH3 and N2O emissions were determined using closed chamber technique and the plants were harvested to measure the dry matter yield and nutrient uptake. The results of the experiment revealed that the UCuZn treatment had the highest dry matter yield, 9.31 g pot-1, and lowest NH3 volatilization, 0.68 mg-NH3. as compared to the other treatments. The combination of EEF treatments with Cu, Zn and DMPP resulted in 35.17 μg g-1 of N2O emission while the EEF treatment with either Cu, Zn or DMPP individually resulted in higher N2O emissions, with the values 51.07, 66.99 and 46.31 μg g-1, respectively. The UCuZnDMPP treatment resulted in reduction of N2O up to 67% compared to urea (control) treatment. To evaluate the effects of the coated urea under field conditions, Mas Madu variety of maize was planted at Ladang 2, UPM, and subjected to five treatments: urea (control), UCuZn, UCuZnDMPP, Ubio and Ug2, over 9 weeks. The site was fertilized with EEF and urea (control), TSP and MOP at the rates of 120, 50 and 100 kg ha-1, respectively. The plants were harvested at 63 days to measure the grain yield. The soil and plant samples were also analyzed for N, Cu and Zn content. The results showed 74.1% and 79.5% improvement in grain yield for the UCuZn and UCuZnDMPP treatments at 7547.3 kg ha-1 and 7688.2 kg ha-1, respectively, as compared to the Urea (control) treatment which only produced 4283.6 kg ha-1. It was thus concluded that the supply of N in correct amounts and at the right time are crucial to obtain maximum efficiency of the N fertilizer, which was before the 8th week of planting. Further, EEF treated with Cu and Zn (urease inhibitors) and DMPP (nitrification inhibitor) can improve N use efficiency by reducing NH3 and N2O emission, and at the same time increase crop production.